Honeypot defense and transmission strategy based on offensive and defensive games in vehicular networks - Jie YI; Tengfei CAO; Shuai GAO; Jianqiang HUANG (网络与信息安全学报)
With the rapid development of the Internet of Vehicles, service providers can efficiently provide caching services for vehicle users by deploying 5G base station-type RSUs adjacent to vehicles.However, due to the presence of malicious attackers, the controlled base station is turned to be malicious for the purpose of identity forgery attack.When messages are sent in the name of malicious base stations to interfere with the communication link between vehicles and the trusted base stations, it is easy to cause serious driving safety problems.To solve the above problem, an efficient transmission and honeypot defense strategy was proposed, which was based on the offensive and defensive game in the Internet of Vehicles to reduce the risk of identity forgery attacks and improve the security of data transmission.The interaction between trusted base stations and malicious base stations in the Internet of Vehicles scenario was modeled as an attack-defense game model.On this basis, trusted base stations and honeypot base stations were jointly used as defenders to defend against malicious attacks.Then, the trusted base station and the malicious base station, as the two sides of the offensive and defensive game, chose their respective strategies to construct a model of the benefit function of both sides.Combined with the vehicle delay feedback mechanism, the defender and the malicious base station dynamically adjusted their respective strategies.By adjusting the interaction between the honeypot base station and the vehicle, and also the degree of IP randomization, the overall benefit of the defender was effectively improved.Besides, the optimal solution was obtained by using the mixed strategy Nash equilibrium theory.Simulation experimental results show that the proposed strategy can improve the secure transmission performance of the Internet of Vehicles service in the presence of malicious attackers, and the defender’s expected benefit is improved by 48.9% and the data transmission delay is reduced by 57.1% compared to the no-honeypot defense scheme.